Racial Passing in Toni Morrison's Novel God Help the Child - Gurung, Gol Man (Interdisciplinary Journal of Management and Social Sciences, 2021)
This paper examines the racial passing in Toni Morrison's God Help the Child. The core concern of this paper is to observe the stories of five characters who turn to be narrator themselves. Their stories revolve around the process of veiling and unveiling their racial identity. Sweetness herself is a daughter of black parents but she considers herself as white because she got lighter skin which gives her confidence to reject her own daughter, Bride who is very black including these kinds of stories regarding racial minority and color as a sense of insecurity. Morrison gives pictorial view of the modern American society. This shows that race is not a fixed category and the people of one race can behave and perform like the people of another race and pose as who actually are not. Blacks may pass as White and White may pass as Blacks and it shows that one can pass as White even though she is Black. It challenges the fixity of race as a category and reveals its fluidity.